Comparison between dicode PPM and offset PPM enhancement with different error correction codes. Issue 8 (5th March 2023) - Al‐batoosh, Ahmed H.; Al‐Nedawe, Basman M.; Hussein, Yasmeen M.
Abstract: Offset pulse position modulation (OPPM) and Dicode pulse position modulation (DiPPM) have been introduced as new attractive modulation techniques, however, they are suffering from erasure, wrong slot, and false alarm errors. in this paper, two types of error correction (EC) codes, Low‐Density Parity Check (LDPC) code and Reed Solomon (RS) code, where paired the OPPM and DiPPM systems to reduce bugs, analyze the best EC parameters, and choose the superlative EC system. In other words, the performance of OPPM engaging LDPC codes and DiPPM employing LDPC codes will be compared against the OPPM engaging RS codes and DiPPM employing RS codes. To systematically carry out this comparison, numbers of photons, transmission efficiency, and the code rate are computed. The evaluation has stated that the data transmission rate at the start has indicated that OPPM with LDPC requires only 1.2 × 10 3 photons/pulse compared to the necessity of 1.821 × 10 3 photons/pulse when the DiPPM used LDPC. Accordingly, the transmission efficiency has been increased due to a reduction of number of photons. Also, the coded OPPM with LDPC codes is better than the coded DiPPM with LDPC codes when operating at a code rate that is approximately 0.7. Abstract :